Susceptibility of young and adult rat kidneys to impacts of mosquito coil fumes. Issue 1 (1st January 2021) - Abdrabouh, Abeer E.
ABSTRACT: The present study aimed to investigate the effect of exposure to mosquito coil fumes (6 hr/day, 6 days/week, for 4 weeks) on the biochemical and histological structure of kidney in young and adult male rats. Atomic analysis of the coil was estimated to indicate the main constituent elements of the coil. Results showed a non-significant change in body weight gain and somatic indices, except for the heart somatic index that increased significantly in both ages compared to control groups. Biochemical analysis showed a significant increase in serum levels of creatinine, urea, uric acid, neutrophil gelatinase-associated lipocalin (NGAL), cystatin C. However, serum total protein content was reduced significantly. Urine analysis showed a marked increase in creatinine, urea, total protein, microalbuminuria, and NGAL, along with a significant reduction at glomerular filtration rate (GFR). Moreover, serum and urine Na + and K + levels showed no obvious changes in both ages compared to control groups, except for serum sodium in the young group. Histopathological examination confirmed the destructive effect of coil fumes on tubules and glomeruli of exposed kidneys, which was obvious in young than adult rats. Thus, inhalation of coil fumes may provide a serious risk on the kidney health of exposed human beings